MiR-199a-5p–HIF-1α-STAT3 Positive Feedback Loop Contributes to the Progression of Non-Small Cell Lung Cancer - Yang, Xingping; Zheng, Yuzhen; Tan, Jian; Tian, Renjiang; Shen, Piao; Cai, Weijie; Liao, Hongying (Frontiers in Cell and Developmental Biology, 2021)
Background: Non-small cell lung cancer (NSCLC) is the most common malignancy worldwide. MiR-199a-5p has been reported to play important roles in multiple tumors, inclusive of NSCLC. However, little is definitively known pertaining to its explicit mechanism of action in NSCLC. Methods: The expressions of miR-199a-5p and hypoxia-inducible factor-1α (HIF-1α) mRNA were quantified employing qRT-PCR. H1299 and A549 cells were transiently transfected with miR-199a-5p mimics or inhibitors. Then, CCK-8 assays, flow cytometry analysis, and Transwell assay were performed for detecting cell proliferation, cell cycle, apoptosis, migration, and invasion of NSCLC cells, respectively. HIF-1α, signal transducer and activator of transcription 3 (STAT3), and p-STAT3 expressions were detected via Western blotting. Bioinformatic analysis and dual-luciferase assay were performed to investigate the interactions among miR-199a-5p, HIF-1α, and STAT3. Xenograft models were established with nude mice for further analyzing the bevacizumab resistance of NSCLC cells. Results: MiR-199a-5p expression was markedly attenuated in NSCLC tissues and cell lines. Overexpression of miR-199a-5p repressed the proliferation, migration, and invasion but induced the apoptosis of NSCLC cells. HIF-1α was identified as a direct target of miR-199a-5p. There was a positive feedback loop among miR-199a-5p, HIF-1α, and STAT3. Co-transfection of HIF-1α or STAT3 overexpression plasmids counteracted the effects of miR-199a-5p. In vivo experiments indicated that the feedback loop was in association with the bevacizumab resistance of NSCLC cells. Conclusion: MiR-199a-5p blocked the progression of NSCLC and sensitized NSCLC cells to bevacizumab by suppressing HIF-1α and STAT3, while the HIF-1α/STAT3 axis suppressed the expression of miR-199a-5p, which forms a positive feedback loop to promote the sustaining progression of NSCLC.